The impact of ultrasonic post-manufacturing on the microstructure of the metallic sheet-based triply periodic minimal surfaces manufactured by electron beam melting; Перспективы развития фундаментальных наук; Т. 1 : Физика - Khrapov D. Dmitriy (2023, 2023)
Заглавие с экрана